Crosstalk Between Metabolic Biomarkers and Pulse Wave Analysis in Hypertensive Patients - Mirela Baba; Mihaela Ioana Maris; Adina Bucur; Daniela Jianu; Simina Mariana Moroz; Dana Stoian; Constantin Tudor Luca; Ioana Mozos (Biomedicines)
Background/Objectives: Hypertension is strongly linked to changes in vascular function and lipid metabolism. This study aimed to examine the relationship between lipid profiles, various metabolic biomarkers, and pulse wave analysis in patients with hypertension. Methods: A group of 66 hypertensive patients, aged 64 ± 10 years, participated in pulse wave analysis utilizing an oscillometric device. Multiple lipid serum biomarkers were assessed, such as total cholesterol (TC), triglycerides (TG), and non-HDL cholesterol (non-HDL). Lipid balance index (LBI) was determined by considering TG, LDL, HDL levels, and lipid-lowering medications. Results: Notable correlations were observed for SBP, DBP, and early vascular aging (EVA) with lipid biomarkers. In addition to serum lipids, metabolic syndrome, insulin resistance, and non-alcoholic fatty liver disease (NAFLD) were significantly linked to pulse wave analysis variables. Multiple regression analysis showed that only TC continued to have a significant association with DBP. Conclusions: Total cholesterol, triglycerides, non-HDL cholesterol, and lipid balance index provide information about systolic and diastolic blood pressure, as well as early vascular aging in hypertensive patients. LBI offers valuable vascular insights in hypertensive individuals with cardiovascular risk factors, early vascular aging, insulin resistance, and NAFLD. The connection between metabolic biomarkers and pulse wave measurements in individuals with hypertension offers a comprehensive method for the early identification of vascular injury and could enhance the prediction of major cardiovascular events.